Schistosomus reflexus condition in Sheep - REDDY, K.RAM CHANDRA (The Indian Journal of Animal Reproduction, 2007)
Cases of scistosomus reflexus in Deccani sheep is reported and managed successfully with caesarean operation. Key word.